Brief description of the linguistic representation of ideological lies in the first post-revolutionary newspapers of Kazakhstan (Eurasian Journal of Philology Science and Education, 2016)
For understanding the current state of the Russian language it is necessary to examine the past of this language, because totalitarian language forced the impact on linguistic consciousness. Newspaper is a channel through which the effective impact of totalitarian ideology on the public consciousness was implemented. The analyzed compressive demagogic texts from the Kazakh newspapers («Golos Semirechja», «Dzhetysuyskaya pravda», «Turkestansky kommunist») shows that each such text conveys a certain ideologem: it contains a combination of two or more ideologies – judgments prescribed by the totalitarian system as an official dogma. One of the most common ideologies is an ideologem of confrontation on the basis of which the picture of the new world is simulated. It is introduced as mandatory and is motivated by a number of extra-linguistic factors: the revolution, class contradictions, external threat, internal threat, reaction victory. The ideologem of enemy is identified and described in this article. It also includes the ideology of class (class struggle), although the image of the enemy is much broader than the concept of the class enemy.
Keywords: lie ideologem; totalitarian language; demagogic texts.